2017
DOI: 10.1080/20008198.2018.1423825
|View full text |Cite
|
Sign up to set email alerts
|

Early indicators of problematic grief trajectories following bereavement

Abstract: Background: Little is known about the development of Prolonged Grief Disorder (PGD) symptoms over time in adults. For clinical purposes, it would be useful to have knowledge about early indicators of a problematic grief trajectory. Objective: This study aimed to identify classes of bereaved individuals with similar trajectories of PGD symptoms and to design a provisional screening tool including symptoms predicting membership of classes with problematic grief trajectories. Method: In a Dutch sample of 166 bere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 17 publications
3
21
0
Order By: Relevance
“…However, no identical PGD‐symptom trajectories have been identified 16‐19 . PGD‐symptom trajectories were identified similar to our trajectories identified as endurance, 16‐19 resilience, 18 prolonged symptomatic, 17,18 and chronically distressed, 19 but labeled differently, that is, resilience, 18 low grief, 16,19 persistent low/moderate PGD symptoms, 17 moderate‐decreasing grief, 19 and decreasing moderate PGD symptoms, 17 acute‐recovery, 18 moderate‐improving, 18 moderate‐stable, 18 and persistently high PGD symptoms, 17 and high grief, 19 respectively. We intentionally used “endurance” to define a group of bereaved caregivers who not only withstood the hardship of bereavement, but also maintained psychological well‐being throughout their first 2 years of bereavement despite losing a beloved.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…However, no identical PGD‐symptom trajectories have been identified 16‐19 . PGD‐symptom trajectories were identified similar to our trajectories identified as endurance, 16‐19 resilience, 18 prolonged symptomatic, 17,18 and chronically distressed, 19 but labeled differently, that is, resilience, 18 low grief, 16,19 persistent low/moderate PGD symptoms, 17 moderate‐decreasing grief, 19 and decreasing moderate PGD symptoms, 17 acute‐recovery, 18 moderate‐improving, 18 moderate‐stable, 18 and persistently high PGD symptoms, 17 and high grief, 19 respectively. We intentionally used “endurance” to define a group of bereaved caregivers who not only withstood the hardship of bereavement, but also maintained psychological well‐being throughout their first 2 years of bereavement despite losing a beloved.…”
Section: Discussionsupporting
confidence: 67%
“…Endurance, transient‐reaction, resilience, and prolonged‐symptomatic trajectories were identified for both PGD and depressive symptoms, whereas symptom trajectories of potential recurrence and chronic distress were uniquely identified for PGD and MDD, respectively. In addition, despite endurance and transient‐reaction trajectories conjointly comprising the most prevalent trajectories for PGD 16‐19 and depressive (see systematic review) 35 symptoms as reported, prevalence rankings of the other trajectories differed between PGD and depressive symptoms (Table 2). The prolonged‐symptomatic trajectory was the third and the least prevalent trajectories for depressive and PGD symptoms, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…These findings underscore that it could be useful to develop means to identify vulnerable subgroups in the first months of bereavement and to offer them preventive interventions. Notably, attempts have been made to devise screening tools to identify such subgroups (Djelantik, Smid, Kleber, & Boelen, 2018). In addition, there is evidence that treatment of people with elevated PCBD in the early months of bereavement can be successful in preventing exacerbations of grief symptoms (Litz et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the synergistic and negative effects of CG and PTSD on clinical impairment (Neria & Litz, ), we hypothesized that one of these groups would have a higher probability for threshold CG and PTSD as well as for clinical impairment. In order to identify factors that predict group membership, we investigated proposed risk (preexisting mental health conditions, other non‐9/11‐related lifetime trauma exposure, and negative interim life events) and protective factors (grief support, social support, perception of income adequacy, and positive interim life events) known to affect grief and trauma‐related disorders, comorbidity, and impairment (Boelen et al., ; Djelantik, Smid, Kleber, & Boelen, ; Galea, Tracy, Norris, & Coffey, ; Heeke et al., ; Joseph, Matthews, & Myers, ; Nickerson et al., ; Nillni et al., ) while controlling for participant age, gender, relationship to the deceased, and education level. To validate the results of the LCA, class membership was examined in relation to distinct distal outcomes, including patterns of alcohol use, and measures of physical and mental health.…”
mentioning
confidence: 99%